Modern ways of solving basic environmental problems - Andrushchenko, S. V. (My University, 2019)
The purpose of the research is to analyze the factors that have a negative impact on both the life of the individual and the environment, as well as suggest methods that can help escape these problems.
Keywords: environmental security state; preserve the ecology; environmental crisis